Biomarkers as a tool for management of immunosuppression in transplant patients - Wieland, Eberhard; Olbricht, Christoph J.; Süsal, Caner; Gurragchaa, Purevtseren; Böhler, Torsten; Israeli, Moshe; Sommerer, Claudia; Budde, Klemens; Hartmann, Bertram Josef; Shipkova, Maria; Oellerich, Michael (Therapeutic drug monitoring, 2010)
Therapeutic drug monitoring is a well-established approach in transplantation medicine to guide immunosuppressive therapy. However, it cannot always predict the effects of immunosuppressive drugs on immune cells, because it does not reflect any aspect of an individual patient's immune system. Pharmacodynamic monitoring is a more recent strategy to provide information about the biologic effect of a specific drug or drug combination on the individual transplant patient. Currently, there is a large number of different biomarkers that either directly (specific markers) or indirectly (global markers) relate to the pharmacodynamic effects of immunosuppressive drugs and are under investigation as potential candidates to be introduced in clinical practice. Such biomarkers may be useful to identify patients at risk of developing acute rejection, infection, or cancer as well as patients who are suitable for minimization of immunosuppressant therapy and may be helpful to manage the timing and rate of immunosuppressant weaning. Serial longitudinal monitoring may allow maintenance of an individualized immunosuppressive regimen. Thus, biomarker monitoring is a potential complementary tool to therapeutic drug monitoring. This review summarizes the current state of knowledge about the use of a number of global or drug-specific pharmacodynamic biomarkers. It is not a comprehensive overview of the literature available, but rather an evidence-based reflection by experts who are intensively involved in scientific work in this field.